Características clínicas, epidemiológicas y ecográficas de los miomas uterinos en el Hospital Regional Docente de Trujillo periodo 2011 - 2015 - Arqueros Juárez, Héctor Luis (2016)
Objective: To describe the epidemiological, clinical, and ultrasound characteristics of uterine fibroids in the Regional Hospital of Trujillo period 2011-2015. Material and Methods: This study is a descriptive design, transversal and retrospective study, the population consisted of 339 medical records of patients diagnosed with uterine fibroids, of which 177 met the inclusion criteria Results: The mean age was 43.7 years, 70.1% were multiparous and 98.3% had no family history and early menarche. In menorrhagia symptoms is at 80.8%, followed by 70.6% pelvic pain, pelvic pressure symptoms then with 33.9% and finally reproductive effects with 15.8% uterine fibroids Sonographically alone showed a 67.8% intramural fibroid with 48.5%, and overall myomas have an average size of 5.9cm. Conclusions: The mean age of patients with uterine fibroids is 43.7 ± 7.2 years, being mostly multiparous no history of early menarche or family history of fibroids. Menorrhagia was the most common clinical manifestation followed by dysmenorrhea and hypogastric discomfort. Sonographically location within the predominant frequency intramural fibroid, relative to the amount found that most were multiple uterine fibroids, and with respect to size were mostly less than 5 cm.